Prolonged Breastfeeding and the Risk of Plasmodium vivax Infection and Clinical Malaria in Early Childhood - MINA-Brazil Study Working Group (2022)
BACKGROUND: Relatively few Amazonian infants have clinical malaria diagnosed, treated and notified before their first birthday, either because they are little exposed to an infection or remain asymptomatic once infected. Here we measure the proportion of children who have experienced Plasmodium vivax infection and malaria by 2 years of age in the main transmission hotspot of Amazonian Brazil. METHODS: We measured IgG antibodies to 3 blood-stage P. vivax antigens at the 1- and 2-year follow-up assessment of 435 participants in a population-based birth cohort. Children's malaria case notifications were retrieved from the electronic database of the Ministry of Health. We used multiple Poisson regression models to identify predictors of serologically proven P. vivax infection and clinical vivax malaria during the first 2 years of life. RESULTS: Overall, 23 [5.3%; 95% confidence interval (CI): 3.5-7.8%) children had antibodies to ≥2 antigens detected during at least one follow-up assessment, consistent with past P. vivax infection(s). Fifteen (3.4%; 95% CI: 2.1-5.6%) children had clinical vivax episodes notified during the first 2 years of life; 7 of them were seronegative. We estimate that half of the infections remained unnotified. Children born to women who experienced P. vivax infection during pregnancy were more likely to be infected and develop clinical vivax malaria, while those breast-fed for ≥12 months had their risk of being P. vivax-seropositive (which we take as evidence of blood-stage P. vivax infection during the first 2 years of life) decreased by 79.8% (95% CI: 69.3-86.7%). CONCLUSION: P. vivax infections in early childhood are underreported in the Amazon, are associated with anemia at 2 years of age, and appear to be partially prevented by prolonged breastfeeding.